Roles of FrxA and RdxA Nitroreductases of Helicobacter pylori in Susceptibility and Resistance to Metronidazole - Jeong, Jin-Yong (American Society for Microbiology, 2001)
The relative importance of the frxA and rdxA nitroreductase genes of Helicobacter pylori in metronidazole (MTZ) susceptibility and resistance has been controversial. Jeong et al. (J. Bacteriol. 182:5082–5090, 2000) had interpreted that Mtz(s) H. pylori were of two types: type I, requiring only inactivation of rdxA to became resistant, and type II, requiring inactivation of both rdxA and frxA to become resistant; frxA inactivation by itself was not sufficient to confer resistance. In contrast, Kwon et al. (Antimicrob. Agents Chemother. 44:2133–2142, 2000) had interpreted that resistance resulted from inactivation either of frxA or rdxA. These two interpretations were tested here. Resistance was defined as efficient colony formation by single cells from diluted cultures rather than as growth responses of more dense inocula on MTZ-containing medium. Tests of three of Kwon's Mtz(s) strains showed that each was type II, requiring inactivation of both rdxA and frxA to become resistant. In additional tests, derivatives of frxA mutant strains recovered from MTZ-containing medium were found to contain new mutations in rdxA, and frxA inactivation slowed MTZ-induced killing of Mtz(s) strains. Northern blot analyses indicated that frxA mRNA, and perhaps also rdxA mRNA, were more abundant in type II than in type I strains. We conclude that development of MTZ resistance in H. pylori requires inactivation of rdxA alone or of both rdxA and frxA, depending on bacterial genotype, but rarely, if ever, inactivation of frxA alone, and that H. pylori strains differ in regulation of nitroreductase gene expression. We suggest that such regulatory differences may be significant functionally during human infection.